KEBIJAKAN PEMERINTAH DAERAH KABUPATEN KAMPAR DALAM PEMBERDAYAAN PETANI KERAMBA DI WADUK PLTA KOTO PANJANG TAHUN 2014-2015 - Afriliska, Rivaldi; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Researchers formulate the problem of research that is why there is no policy of Kampar regency government in empowering keramba farmers in Koto Panjang hydropower reservoir. This research uses qualitative research methods with descriptive research type, which can be interpreted as problem-solving process investigated by describing the state of the research subject based on the facts that appear during the study which then continued with based on the existing theories. Based on the results of the research is known Empowerment of fishery business by the Regional Government of Kampar regency on fish farmers in Koto Panjang hydropower dam does not run as empowerment in other areas. It is seen that there is no assistance and programs that run and is destined for fish farmers in Koto Panjang hydropower reservoir. Empowerment of fishery business is not maximally done by local government especially in fishery potential in Koto Panjang hydropower reservoir, less maximal cost or budget for empowering fishery businessKeywords: Policy, Empowerment, Fish Farmers